Berkumpul selama masa pandemi - Vashti, Islamey Triesa (Journal of Placemaking and Streetscape Design, 2024)
Covid-19 has been present in Indonesia, including DKI Jakarta, for approximately 1 year. PSBB policies were implemented to reduce the increasing number of cases every day, supported by other policies. On June 5, 2020, the Jakarta provincial government issued the transitional PSBB policy, marking the beginning of the new normal era. Entertainment venues were gradually reopened by the government with the aim of restoring the economy. Many people went on vacations and gathered in private and public spaces around their residences despite the continued advice and dangers of the pandemic. The research methods used were participant observation, in-depth interviews, and literature studies conducted from October to May 2021, with the policy dynamics ranging from transitional PSBB to Micro PPKM. The data collection took place on Pelangi Street, Pejaten, Jakarta, Indonesia, with informants selected as mothers residing on Pelangi Street. The mothers on Pelangi Street continued to engage in collective activities based on trust among fellow participants. Some activities they engaged in together included exercise, savings groups, and gatherings. These activities were carried out with the aim of boosting immunity and resistance to Covid-19. To protect themselves and comply with government regulations, they continued to wear masks as an effort to protect themselves from Covid-19, despite contravening government protocols and advisories to stay at home. In reality, gathering during the pandemic not only involves the lack of information or knowledge or even the indifference of the community, but it is highly complex, involving neighborly life and cognitive schemas.